Debridement, Antibiotics, and Implant Retention for an Early Periprosthetic Infection After Unicompartmental Knee Arthroplasty: A Technical Note - Mohammed Anter Abdelhameed, MD; Yaser E. Khalifa, MD, PhD; Hatem M. Bakr, MD, PhD; Mohammad Kamal Abdelnasser, MD, PhD (Arthroplasty Today, 2022)
Early periprosthetic joint infection in unicompartmental knee arthroplasty (UKA) is shown to have a detrimental effect on the success of UKA surgery not only because of the sequences of the infection but also due to the other healthy lateral compartment. It is well known that Oxford meniscal bearing UKA is a very precise procedure that the use of any excessive force may have an injurious effect on the future prosthesis stability with a higher risk of bearing dislocation. This technical note aims at describing how to deal with a case of early periprosthetic joint infection in a female patient who underwent debridement, wash, implant retention and change of the mobile bearing insert including the demonstration of a difficult step during this procedure.